2002
DOI: 10.1182/blood.v100.3.1084
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin inhibits macropinocytosis and mannose receptor–mediated endocytosis by bone marrow–derived dendritic cells

Abstract: IntroductionDendritic cells (DCs) arise from CD34 ϩ bone marrow (BM) stem cells and represent a heterogenous population of ubiquitously distributed antigen-presenting cells (APCs) that play critical roles as initiators and modulators of immune responses. 1,2 Among the most striking features underlying the efficiency of DCs as APCs is their unsurpassed capacity to take up antigens via constitutive macropinocytosis and mannose receptor-mediated endocytosis 3 and to subsequently process and present major histocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 29 publications
11
131
2
Order By: Relevance
“…11 In this context, Rapa can inhibit dendritic cell activity as well as chemokine-dependent leukocyte migration, both of which are major components of the inflammatory response. 25,26 We found that Rapa impaired hepatic cytokine expression at the mRNA level after cell transplantation, including that of monocyte chemotactic protein 1 mRNA, which mediates monocyte/macrophage chemotaxis, as well as mRNAs of macrophage inflammatory protein 2 and cytokine-in- duced neutrophil chemoattractant, both of which are potent neutrophil chemoattractants. Cell engraftment in Rapa-treated rats most likely benefited from these perturbations, similar to the depletion of Kupffer cells in earlier studies, 11 although our studies did not verify changes in cytokines at the protein level.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…11 In this context, Rapa can inhibit dendritic cell activity as well as chemokine-dependent leukocyte migration, both of which are major components of the inflammatory response. 25,26 We found that Rapa impaired hepatic cytokine expression at the mRNA level after cell transplantation, including that of monocyte chemotactic protein 1 mRNA, which mediates monocyte/macrophage chemotaxis, as well as mRNAs of macrophage inflammatory protein 2 and cytokine-in- duced neutrophil chemoattractant, both of which are potent neutrophil chemoattractants. Cell engraftment in Rapa-treated rats most likely benefited from these perturbations, similar to the depletion of Kupffer cells in earlier studies, 11 although our studies did not verify changes in cytokines at the protein level.…”
Section: Discussionmentioning
confidence: 97%
“…Experiments were repeated at least twice for reproducing results.Tx, transplantation. (25,50, and 100 mg/kg/d) were used either alone or in combination (n ϭ 3 DPPIV Ϫ rats each). By themselves, Tacro, Rapa, or MMF in these dosages did not yield allograft survival to 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…fluorescein (DexFITC) were obtained from Molecular Probes. The conditions for Ag uptake were chosen based upon methods used in similar studies (37,38). At day 7, BMDC were harvested from DEF medium cultures and washed with PBS.…”
Section: Ova and Dextran Uptakementioning
confidence: 99%
“…In the cell, Rapamycin binds to FKBPs (FK506 binding proteins), a speciWc family of cytosolic proteins (immunophilins) [17,18]. It is known that mTOR inhibition in APCs during the time of culturing attenuates cytokine production and surface marker expression as well as it prevents macropinocytosis and receptor mediated endocytosis [16]. Additionally, in higher doses Rapamycin induces apoptosis.…”
Section: Mtor Inhibition Results In Total Impairment Of Dalis Formationmentioning
confidence: 99%
“…Rapamycin, the potent inhibitor for the mammalian target of Rapamycin (mTOR), is previously described as immunosuppressive drug [16]. This macrolide antibiotic, produced by Streptomyces hygroscopicus, was introduced to prevent allograft rejection.…”
Section: Mtor Inhibition Results In Total Impairment Of Dalis Formationmentioning
confidence: 99%